Evaluation of Jatropha curcas L. leaves mulching on wheat growth and biochemical attributes under water stress - Irshad, Muhammad; Ullah, Faizan; Fahad, Shah; Mehmood, Sultan; Khan, Asif Ullah; Brtnicky, Martin; Kintl, Antonin; Holatko, Jiri; Irshad, Inam; El-Sharnouby, Mohamed; El Sabagh, Ayman; Datta, Rahul; et al. (BMC plant biology, 2021)
BACKGROUND: Organic mulches are widely used in crop production systems. Due to their benefits in improving soil fertility, retention of soil moisture and weed control. Field experiments were conducted during wheat growing seasons of 2018-2019 and 2019-2020 to evaluate the effects of Jatropha leaves mulch on the growth of wheat varieties 'Wadan-17' (rainfed) and 'Pirsabaq-2013' (irrigated) under well irrigated and water stress conditions (non-irrigated maintaining 40% soil field capacity). Jatropha mulch was applied to the soil surface at 0, 1, 3 and 5 Mg ha-1 before sowing grains in the field. Under conditions of water stress, Jatropha mulch significantly maintained the soil moisture content necessary for normal plant growth. RESULTS: We noted a decrease in plant height, shoot and root fresh/dry weight, leaf area, leaf relative water content (LRWC), chlorophyll, and carotenoid content due to water stress. However, water stress caused an increase in leaf and root phenolics content, leaf soluble sugars and electrolytes leakage. We observed that Jatropha mulch maintained LRWC, plant height, shoot and root fresh/dry weight, leaf area and chlorophyll content under water stress. Moreover, water stress adverse effects on leaf soluble sugar content and electrolyte leakage were reversed to normal by Jatropha mulch. CONCLUSION: Therefore, it may be concluded that Jatropha leaves mulch will minimize water stress adverse effects on wheat by maintaining soil moisture and plant water status.
Keywords: listy rostlin; Triticum; Electrolyte leakage; Plant Roots; Water stress; Chlorophyll; Soluble sugars; pšenice; dehydratace; Jatropha; Soil; kořeny rostlin; Mulch; chlorofyl; Phenolics; Crop Production; Carotenoids; Dehydration; Plant Leaves; metabolismus sacharidů; pěstování plodin; půda; Carbohydrate Metabolism; karotenoidy